Theoretically Modified Optical Length Research on the Physical Boundary of the Double-Heterogeneous System - Lei, Lou; Xiaoming, Chai; Dong, Yao; Lianjie, Wang; Mancang, Li; Liang, Chen; Xiaoli, Liu; Hongbo, Zhang; Sinan, Li; Xiao, Tang; Nan, Zhou (Frontiers in Energy Research, 2022)
Because of the double-heterogeneity (DH), dispersed particle-type systems cannot be described by traditional neutronic programs, and the volumetric homogenization method (VHM) will bring reactivity calculation deviation because of ignoring the spatial self-shielding effect of the particles. In this article, the relationship between the reactivity calculation deviation and the optical length of dispersed particle-type fuel and different types of burnable poisons is analyzed. Also then, it was proposed that the influencing factors of reactivity calculation deviation can be integrated to a physical quantity named theoretically modified optical length containing the influencing factors mentioned earlier. In addition, the DH physical boundary has forward that, when the theoretically modified optical length is larger than 10−4, reactivity calculation deviation of volumetric homogenization method will be larger than 100 pcm, and the DH of the dispersed particle-type systems should be considered.